180k views
2 votes
Please help me I’m so lost !!!!

Please help me I’m so lost !!!!-example-1
User Aloraman
by
5.6k points

1 Answer

4 votes

Answer:


4095

Explanation:


\sum _(n=1)^63\left(4^(n-1)\right)\:


\sum _(n=1)^63\cdot \:4^(n-1)

Compute general progression:


(3\cdot \:4^(\left(n+1\right)-1))/(3\cdot \:4^(n-1))=4


r=4\\


a_1=3\cdot \:4^(1-1)


a_1=3

nth term is computed by:


r=4,\:a_n=3\cdot \:4^(n-1)

plug in the values
n=6,\:\spacea_1=3,\:\spacer=4:


=3\cdot (1-4^6)/(1-4)


=4095

User Donel
by
5.4k points